International and interdisciplinary perspectives on Eric Voegelin (Univ. of Missouri Press, 1997)
Eric Voegelin's analysis of the history of political order and disorder has had an enormous impact on the fields of political science, philosophy, religion, history, and sociology. The collection explores the evolution of Voegelin's theory from his history of political ideas of the 1940s to his philosophy of consciousness of the 1980s. Adding significantly to our understanding of the development of Voegelin's work, these essays compare and contrast it to that of his contemporaries such as Husserl and Schutz as well as to that of recent scholars, including Lonergan and Levinas.